SIGNIFICANCE OF ISCHEMIA-MODIFIED ALBUMIN AS A SIMPLE MEASURE OF OXIDATIVE STRESS AND ITS DISCRIMINATORY ABILITY IN DIABETIC RETINOPATHY: Literature Review and Meta-Analysis. Issue 6 (June 2016) - Seshadri Reddy, Varikasuvu; Sethi, Sumita; Gupta, Navdeep; Agrawal, Poonam; Chander Siwach, Ram
Abstract : Purpose: Oxidative stress (OXS) plays critical role in the development of diabetic retinopathy (DRP). Increased concentrations of serum ischemia-modified albumin (IMA) have been demonstrated as a novel and inexpensive measure of oxidative stress. Although few pilot studies have reported increased IMA in DRP, the available literature is limited to comprehensively describe the potential significance of IMA in predicting DRP. Methods: The authors performed a meta-analysis to investigate IMA in DRP compared with control and diabetes mellitus subjects. The authors also performed a meta-analysis of area under curve for IMA. PubMed (Medline), Embase, Scopus, Web of Science, Science Direct, Springer Link, and Google Scholar databases were searched for relevant studies in serum IMA in DRP. The authors obtained five observational studies. Meta-analysis was performed using Review Manager 5.3 and MEDCALC 15.8 software to present the pooled-overall effect size as standardized mean difference and overall area under curve value of IMA. Results: Random-effects meta-analysis indicated a significant increase in serum IMA in patients with DRP compared with control (standardized mean difference = 2.48, P < 0.0001) and diabetes mellitus groups (standardized mean difference = 1.43, P < 0.0001). Our results also show that IMA can significantly predict the development of DRP (area under curve = 0.86, P < 0.001). Conclusion: Serum IMA may be useful as a simple marker in monitoring of oxidative stress status in DRP and showed significant discriminatory ability in DRP. Future comparative studies in large are needed to further investigate IMA in different types of DRP; proliferative and nonproliferative. Abstract : Supplemental Digital Content is Available in the Text.This meta-analysis, first of its kind, shows serum ischemia-modified albumin as a simple measure of increased oxidative stress in diabetic retinopathy patients as compared with nondiabetic controls and diabetic patients without retinopathy. Importantly, the higher ischemia-modified albumin level has discriminatory ability in diabetic retinopathy with a statistically significant ( P < 0.001) pooled area under curve value.